2016
DOI: 10.12890/2015_000341
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole-related Symptomatic Hyponatremia

Abstract: Hyponatremia is the most common electrolyte balance disorder, especially in the elderly and polymedicated population. The authors report the case of an 83-year-old man with symptomatic severe hyponatremia due to Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) related to pantoprazole. Pantoprazole was discontinued and serum sodium levels reached normal values in two months. To the authors' knowledge, this is the second reported case of pantoprazole-related hyponatremia and, while most patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Hyponatremia is a reported risk in human populations administered PPI with cases suggesting that age may play a role (12). In our study, hyponatremia was only observed in one animal Difference described post-administration levels minus pre-administration baseline.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Hyponatremia is a reported risk in human populations administered PPI with cases suggesting that age may play a role (12). In our study, hyponatremia was only observed in one animal Difference described post-administration levels minus pre-administration baseline.…”
Section: Discussionmentioning
confidence: 45%
“…When used in humans for therapy, multiple adverse events have been reported from patients administered PPIs, mainly skin reactions, nephritis, pancytopenia, anaphylaxis, edema, hepatotoxicity, as well as biochemical changes such as hyponatremia and hypomagnesemia (8)(9)(10)(11)(12)(13)(14). Pantoprazole specifically has been associated with thrombocytopenia, hepatotoxicity, and pancreatitis (9,11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…However, with long-term use several adverse effects are reported, such as a changed gut microbiome, fundic mucosal hypertrophy, Clostridium difficile infection, vitamin B12 deficiency, hypomagnesemia, and acute interstitial nephritis [11]. There are only a few reports on PPI-induced hyponatremia with either omeprazole or pantoprazole [12][13][14][15]. Durst et al reported the reoccurrence of hyponatremia after reintroducing omeprazole [12].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs are often considered devoid of ADRs (Nachnani et al 2015 ) and are liberally prescribed (Falhammar et al 2019b ). Most published case reports of PPI-induced HN were related to the use of omeprazole and esomeprazole (Ferreira et al 2016 ; van der Zalm et al 2020 ) which are also viewed as the PPIs with the highest risk for this overall rare PPI-induced ADR (Falhammar et al 2019b ). Lansoprazole was first reported to be involved in HN in 2000 (Fort et al 2000 ), while indications of pantoprazole-induced HN arose in 2014 (Naharcý et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%